Assessment of the suitability of blood samples collected for toxicology for subsequent genetic analysis: A follow-up study after five years - Grobbelaar, Jana (Department of Pathology, 2024)
Therapeutic and recreational drug use is a common occurrence across the world. However, substance use may sometimes result in adverse drug reactions and death even when typically non-fatal drug doses are administered. This phenomenon may be caused by variants in the genes encoding drug-metabolising enzymes, which leads to altered drug metabolism and at times, toxicity. Cause or manner of death may not be apparent in these cases, even after conducting a standard autopsy and ancillary toxicological and histological investigations. A molecular autopsy may then be performed to identify an underlying genetic cause. Genetic testing is however not routinely conducted in forensic mortuaries, and historic backlogs within the National Forensic Chemistry Laboratories may delay the processing of toxicology samples by months or even years. As such, specimens that have undergone toxicological testing and were stored long-term are sometimes the only samples available to conduct subsequent molecular autopsies, should it be necessary for the cause of death determination. This study therefore aimed to assess whether blood specimens that were used for toxicological analyses could provide suitable DNA for downstream genetic analyses after an extended storage period of five years. In 2017, DNA was analysed from blood samples collected into vials containing sodium fluoride/potassium oxalate preservatives or vials without preservatives (grey and red top tubes, respectively). A subset of these vials underwent preparation for toxicological analyses at the time, prior to DNA extraction, while the remaining tubes underwent DNA extraction immediately and were stored in a molecular laboratory as controls. DNA analysis was then repeated one year later in a separate study, as well as five years later as part of the current study. DNA quantity and quality scores were significantly lower in red top tubes compared to grey top tubes, and toxicological processing did not significantly influence results. DNA concentration and quality also significantly decreased over time for all sample types. PCR amplification and Sanger sequencing results were mostly poor for red top tubes, but grey top tubes showed overall improvements in sequence quality. However, all DNA analysis results generally improved when DNA was extracted using a modified salting out method. Based on these results, it is suggested that forensic laboratories that often experience delays in sample processing should perform molecular autopsies using blood stored in sodium fluoride/potassium oxalate preservative coupled with a salting out DNA extraction method.